Photodynamic Therapy 405 nm Diode Laser as Antibacterial for Cavity and Root Canal Sterilization - Tasya Nafatila Chalisha; Nadira Nurin Febrianti; Sri Kunarti; Setyabudi Setyabudi (Conservative Dentistry Journal, 2021)
Background: The goals of caries restoration and endodontic treatment are to repair and prevent the infection fromgetting worse and if possible, heal the damaged tissue. To achieve this goal, it is necessary to control the presence ofmicrobes in the cavity or root canals with chemo mechanics prior to filling or obturation of the root canals. Disinfectionmethods using disinfectants with effective bactericidal activity are mostly used at subtoxic levels and at concentrationswhere their toxicity is a significant factor. In addition, the disinfection method is considered unable to achieve thoroughcavity cleaning and causes secondary infection. A new method to provide better disinfection without cytotoxic effectshas recently been discovered using the photodynamic method of 405 nm diode laser therapy. Research continues and isprogressing with the existence of various factors that affect the effectiveness of the 405nm diode laser as an antibacterial.Purpose: To evaluate the results of research on photodynamic diode laser therapy with a wavelength of 405 nm as acombination antibacterial therapy in cavity and root canal sterilization techniques. Review(s): Literature study in the formof narrative review using libraries obtained through the PubMed and Google Scholar databases. The optimal bacterialmortality was influenced by the form factor of the target bacteria, the energy dose and duration of laser exposure, and thetype of photosensitizer used. Conclusion: The use of a 405 nm diode laser with an energy power of 50 mW with a distanceof 20 mm can degrade biofilms Streptococcus mutans up to 100% using erythrosine photosensitizer, for 75 seconds. Andwith the same power and distance, it can degrade the biofilm of bacteria Enterococcus fecalis up to 97.51%, using aphotosensitizer chlorophyll, for 120 seconds.